Selective placement of magnetic Fe3O4 nanoparticles into the lamellar nanostructure of PS-b-PMMA diblock copolymer. (July 2015) - Barandiaran, I.; Kortaberria, G.
Graphical abstract: Highlights: Successful anchoring of PMMA brushes to magnetic nanoparticles. Modified nanoparticles selectively placed onto PMMA domains of copolymer. Morphology change from lamellar to lamellar/hexagonally packed cylinders mixture. Abstract: The aim of this work is to obtain a good and selective dispersion of Fe3 O4 magnetic nanoparticles into the lamellar morphology of PS- b -PMMA diblock copolymer. The addition of unmodified nanoparticles inhibited the formation of the lamellar nanostructure obtained for the neat copolymer. Nanoparticles were then modified with 3-methacryloxypropyltrimethoxysilane (MPTS) in order to increase compatibility with PMMA block. Modification was probed by infrared spectroscopy and thermogravimetric analysis, while morphologies were analyzed by atomic force microscopy. Lamellar morphology was maintained but big nanoparticle agglomerates were found. Finally, nanoparticles were modified with PMMA brushes by grafting through technique, obtaining nanocomposites with lamellar morphology in which modified nanoparticles were selectively placed into PMMA domains of the block copolymer. For the nanocomposite with the higher nanoparticle amount, lamellar morphology started to change from lamellar to a mixture of lamellar and hexagonally packed cylinders, probably due to the change in volume fraction among blocks promoted by the presence of a higher amount of nanoparticles in PMMA domains.